Influence of PPAR-alpha agonist fenofibrate on insulin sensitivity and selected adipose tissue-derived hormones in obese women with type 2 diabetes - Anderlová, K; Dolezalová, R; Housová, J; Bosanská, L; Haluzíková, D; Kremen, J; Skrha, J; Haluzík, M (Physiological research, 2007)
PPAR-alpha agonists improve insulin sensitivity in rodent models of obesity/insulin resistance, but their effects on insulin sensitivity in humans are less clear. We measured insulin sensitivity by hyperinsulinemic-isoglycemic clamp in 10 obese females with type 2 diabetes before and after three months of treatment with PPAR-alpha agonist fenofibrate and studied the possible role of the changes in endocrine function of adipose tissue in the metabolic effects of fenofibrate. At baseline, body mass index, serum glucose, triglycerides, glycated hemoglobin and atherogenic index were significantly elevated in obese women with type 2 diabetes, while serum HDL cholesterol and adiponectin concentrations were significantly lower than in the control group (n=10). No differences were found in serum resistin levels between obese and control group. Fenofibrate treatment decreased serum triglyceride concentrations, while both blood glucose and glycated hemoglobin increased after three months of fenofibrate administration. Serum adiponectin or resistin concentrations were not significantly affected by fenofibrate treatment. All parameters of insulin sensitivity as measured by hyperinsulinemic-isoglycemic clamp were significantly lower in an obese diabetic group compared to the control group before treatment and were not affected by fenofibrate administration. We conclude that administration of PPAR-alpha agonist fenofibrate for three months did not significantly affect insulin sensitivity or resistin and adiponectin concentrations in obese subjects with type 2 diabetes mellitus. The lack of insulin-sensitizing effects of fenofibrate in humans relative to rodents could be due to a generally lower PPAR-alpha expression in human liver and muscle.
Keywords: Resistin; Female; Fenofibrate; adiponektin; výsledek terapie; ženské pohlaví; triglyceridy; PPAR gama; Diabetes Mellitus, Type 2; Obesity; Time Factors; časové faktory; Adiponectin; Triglycerides; lidé; Blood Glucose; diabetes mellitus 2. typu; studie případů a kontrol; Treatment Outcome; Adipokines; glykemický clamp; Glycated Hemoglobin A; Humans; obezita; Hypolipidemic Agents; Case-Control Studies; hypolipidemika; Insulin Resistance; Cholesterol, HDL; index tělesné hmotnosti; HDL-cholesterol; glykovaný hemoglobin; inzulinová rezistence; fenofibrát; resistin; tuková tkáň; Glucose Clamp Technique; Adipose Tissue; Body Mass Index; krevní glukóza; Glycated Hemoglobin; PPAR gamma; adipokiny